The modeling of the heat balance elements of construction jet-grouting machines - Novikov V.I.; Pushkarev A.E.; Vorontsov I.I. (Научно-технический вестник Брянского государственного университета)
The article discusses the methods of constructing mathematical models describing the heat balance in the “hydraulic puller-drill shaft” node used in jet-grouting machines during high pressure transmission from stationary elements to rotating parts of the mechanism. The main heat fluxes, which include the heat flux in the hydraulic removal system; heat flow to the water-cement mixture, heat flow to the pre-compression mechanism, heat flow to the drill shaftand methods for solving the heat conduction equation for calculating the temperature field distribution that are formed during the operation of this structural unit are shown.Thus, the proposed modeling technique will allow us to consider and calculate the heat balance of the designed structural jet-grouting unit of ultrahigh pressure, as a set of heat fluxes generated during the operation of this device, considering it as heat sources, from which heat transfer occurs during the operation of the «hydraulic puller», a sealing element, which will ensure predictability of design characteristics of the device design and increase their efficiency. This approach makes it possible to more fully consider the existing main heat fluxes and more accurately simulate the heat balance as part of the assessment of the stress-strain state of ultra-high pressure jet-grouting devices.